Resolvendo a equação do 1º grau encontramos o valor de y igual: 7y – 3 = y + 6 +3y
Soluções para a tarefa
Respondido por
0
Resposta:
y = 3
Explicação passo-a-passo:
7y - 3 = y + 6 + 3y
7y - 3 = 4y + 6
7y - 3 - 4y = 6
3y - 3 = 6
3y = 6 + 3
3y = 9
y = 9/3 por 3
y = 3
espero ter ajudado, bons estudos :)
raianeleite0312:
Muito obrigado
Perguntas interessantes
Química,
9 meses atrás
Matemática,
9 meses atrás
Ed. Física,
9 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Química,
1 ano atrás
Lógica,
1 ano atrás